Mathematics teachers' perceptions of socio-cultural diversities in the classroom - Safura Meeran; Micheal Moos Van Wyk (Journal of Pedagogical Research, 2022)
Mathematics results in South Africa are of serious concern. The reports by TIMSS [Trends in International Mathematics and Science Study] prove that the teaching of mathematics remains a challenge in the South African schooling system. In their attempts to improve mathematics results and to cope with the many curriculum changes since the start of democracy in 1994, mathematics teachers are experiencing increased levels of stress and anxiety. Diversity is a critical issue in education and learners suffer the consequences if teachers do not recognise the importance of diversity. Democracy leads to curriculum change and causes socio-cultural diversity among the learners in a classroom. Mathematics teachers faced ousting of their power in the classroom through the learner-centred strategies that they were expected to implement. In this study, three semi-structured interviews and a focus group discussion were deployed to generate data. The dualistic theoretical lenses used in this paper are based on the theory of culturally responsive teaching and theory of cultural capital. The findings that emerged from the data show that mathematics teachers are ill-equipped to meet the needs of the socio-culturally diverse learners in their differing classrooms. Further research in exploring ethnomathematics as a culturally responsive teaching strategy will reveal new dynamics in socio-cultural deficit thinking.